Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1074/jbc.m412055200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ARD1 Function in Hypoxia Response Using Retroviral RNA Interference

Abstract: Cellular hypoxia response is regulated at the level of hypoxia-inducible factor (HIF) activity. A number of recently identified oxygen sensors are HIF-modifying enzymes that respond to low oxygen by altering HIF modification and thus lead to its activation. In addition to the HIF proline hydroxylases and asparagine hydroxylases, ARD1 is recently described as a HIF-1␣ acetylase that regulates its stability. We found that ARD1 is downregulated in a number of cell lines in response to hypoxia and hypoxia mimic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
70
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 32 publications
8
70
0
1
Order By: Relevance
“…However, the role of ARD1 in the regulation of HIF1a has been contradictory in that both the overexpression and silencing of ARD1 has no impact on the stability of HIF-1 or the mRNA levels of downstream target genes of HIF-1 (Bilton et al, 2005;Fisher et al, 2005). Recently, we showed that mARD1 225 -induced acetylation was repressed under hypoxia or in the presence of metastasis-associated protein 1 (Yoo et al, 2006), which strongly supports the role of ARD1 in the regulation of HIF-1a stability.…”
Section: -Mp Increases the Capillary-tube Formation Of Human Umbilicsupporting
confidence: 52%
“…However, the role of ARD1 in the regulation of HIF1a has been contradictory in that both the overexpression and silencing of ARD1 has no impact on the stability of HIF-1 or the mRNA levels of downstream target genes of HIF-1 (Bilton et al, 2005;Fisher et al, 2005). Recently, we showed that mARD1 225 -induced acetylation was repressed under hypoxia or in the presence of metastasis-associated protein 1 (Yoo et al, 2006), which strongly supports the role of ARD1 in the regulation of HIF-1a stability.…”
Section: -Mp Increases the Capillary-tube Formation Of Human Umbilicsupporting
confidence: 52%
“…GST, glutathione-S-transferase; HBx, HBV regulatory protein; HIF-1a, hypoxia-inducible factor-1a; ODD, oxygen-dependent degradation; WT, wild type. Jeong et al, 2002;Qian et al, 2006), the acetylation hypothesis remains controversial since human ARD1 does not, at least directly, acetylate HIF1a (Arnesen et al, 2005;Bilton et al, 2005Bilton et al, , 2006Fisher et al, 2005;Murray-Rust et al, 2006). Instead, diverse other mechanisms have been proposed for the HDAC inhibitor-induced HIF-1 regulation; Kong et al (2006) showed that HDAC inhibitors induced the proteasomal degradation of HIF-1a by interacting with HSP70 and thereby disrupted the HSP70/HSP90 axis function.…”
Section: Discussionmentioning
confidence: 99%
“…However, its function in mammalian cells has not been defined. Recently, Fisher et al (12) showed that hARD1 knockdown is correlated with the down-regulation of proliferative genes and up-regulation of antiproliferative genes. Because the expressions of HIF-1-regulated genes were not found to be affected by the small interfering RNA (siRNA), hARD1 was suggested to be directly linked to cell proliferation, regardless of HIF-1.…”
Section: Introductionmentioning
confidence: 99%